GENERAL INFORMATION ABOUT CEPHALOSPORINS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Cephalosporins are β-lactam antimicrobials used to manage various infections caused by both gram-positive and gram-negative bacteria. The 5 generations of cephalosporins demonstrate efficacy in treating skin and soft tissue infections, pneumonia, meningitis, and other infections. Cefiderocol is a novel siderophore cephalosporin that exhibits remarkable antibacterial activity.